2004
DOI: 10.1177/001698620404800302
|View full text |Cite
|
Sign up to set email alerts
|

Social Self-Concept, Social Attributions, and Peer Relationships in Fourth, Fifth, and Sixth Graders Who Are Gifted Compared to High Achievers

Abstract: Socially related self-concept, attributions for social success and failure, and peer relationships were investigated for fourth through sixth graders identified as intellectually gifted and a comparison group of high achievers not identified as gifted. The group identified as gifted scored significantly higher on 3 of 4 socially related self-concept subscales ( p < .01) and on the general self-concept scale ( p < .05) of the Self-Description Questionnaire-I (Marsh, 1988). On the Student Social Attributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
2
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 29 publications
6
66
2
6
Order By: Relevance
“…The fact that overall no differences were found for the gifted children on most components of wellbeing (differences were found in subgroups), may partly be explained by the large heterogeneity of the group and also the age of the children might have played a role (Mooij, Hoogeveen, Driessen, Van Hell, & Verhoeven, 2007). The children in this study were younger than in most other studies (Bain & Bell, 2004;Vialle et al, 2007). Lee et al (2012), who also included young children, did not find a difference either.…”
Section: Limitationscontrasting
confidence: 78%
See 1 more Smart Citation
“…The fact that overall no differences were found for the gifted children on most components of wellbeing (differences were found in subgroups), may partly be explained by the large heterogeneity of the group and also the age of the children might have played a role (Mooij, Hoogeveen, Driessen, Van Hell, & Verhoeven, 2007). The children in this study were younger than in most other studies (Bain & Bell, 2004;Vialle et al, 2007). Lee et al (2012), who also included young children, did not find a difference either.…”
Section: Limitationscontrasting
confidence: 78%
“…However, other studies found that both groups did not differ on measures of psychological well-being (Bain & Bell, 2004;Lee, Olszewski-Kubilius, & Turner Thomson, 2012;Shechtman & Silektor, 2012). Also, Neihart et al (2002) concluded that gifted children were at least as robust as any other group regarding well-being.…”
Section: Well-being Of the Giftedmentioning
confidence: 96%
“…Essa correlação pode ser explicada pelo fato dessa classe de habilidade social se referir a comportamentos que demonstram compromisso da criança com as tarefas e com as pessoas no ambiente escolar. É mais provável que crianças dotadas entendam as instruções dos professores e sejam capazes de realizarem as tarefas solicitadas obtendo acentuado sucesso acadêmico (Bain & Bell, 2004) e, com isso, maior satisfação com o ambiente escolar. A forte correlação entre os escores de Responsabilidade e o indicador de Não violência pode também indicar o papel protetor dessas habilidades no contexto escolar especialmente as de seguimento de regras e instruções e de uso adequado do tempo livre.…”
Section: Discussionunclassified
“…Os resultados evidenciam que, em geral, existe um comprometimento de habilidades sociais nas diferentes categorias de crianças e adolescentes com necessidades educacionais especiais (Angélico & Del Prette, 2011;Barreto, Freitas, & Del Prette, 2011;Costa & Del Prette, 2012;Gresham, Lane, MacMillan, & Bocian, 1999;Thomas, Shapiro, DuPaul, Lutz, & Kern, 2011;Wauters & Knoors, 2008). Uma exceção a essa tendência pode ser observada somente em crianças dotadas e talentosas, ainda que os resultados produzidos pelos estudos de caracterização do repertório social dessa população permaneçam contraditórios e inconclusivos (Bain & Bell, 2004;Lehman & Erdwins, 2004;Versteynen, 2001).…”
unclassified